2013
DOI: 10.2478/bvip-2013-0018
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Beta-Endorphin on Oxygen Activity of Neutrophils and Total Antioxidant Status in Rats after Chronic Administration of Methimazole

Abstract: The aim of the study was to evaluate the effect of β-endorphin on oxygen activity of polimorphonuclear neutrophils and to investigate the total antioxidant status of blood serum in rats subjected to chronic treatment with methimazole. The study was carried out on 15 male Wistar rats weighing 270-290 g, divided into two groups. The animals from experimental group were administered a 0.05% drinking water solution of methimazole. The oxygen activity of peripheral blood neutrophils was examined using a modified RB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…It may attend cases of inappropriately conducted treatment of hyperthyroidism with methimazole (the treatment of choice) or with other antithyroid drugs (7, 14). This disease causes numerous multisystemic complications, not sparing the gonads; however, there are few studies that might explain its impact on testicular function, and none of them accurately defines the type of hormonal imbalance in the pituitary-testicular axis (1, 4, 6, 9-11, 20, 27). Ai et al .…”
Section: Introductionmentioning
confidence: 99%
“…It may attend cases of inappropriately conducted treatment of hyperthyroidism with methimazole (the treatment of choice) or with other antithyroid drugs (7, 14). This disease causes numerous multisystemic complications, not sparing the gonads; however, there are few studies that might explain its impact on testicular function, and none of them accurately defines the type of hormonal imbalance in the pituitary-testicular axis (1, 4, 6, 9-11, 20, 27). Ai et al .…”
Section: Introductionmentioning
confidence: 99%
“…β-endorphin is an endogenous opioid that acts as a stress-relieving factor [41]. The opioid system plays an important role in regulating the pro-oxidative and anti-oxidative balance [42]. In this study, serum β-endorphin levels was significantly increased after immobilization stress.…”
Section: Discussionmentioning
confidence: 61%
“…This was despite an increase in flexibility of the testes. Our earlier data suggested that methimazole significantly modulates the production of reactive oxygen species, or stimulates the mechanisms of anti-free radical defence and that this is one of the protective actions of this medicine, whereas oxidative stress is an important cause of testicular damage and infertility in males (10, 22).…”
Section: Discussionmentioning
confidence: 99%
“…In the course of many pathological metabolic conditions, these properties change and can influence the biophysical features of organs. Iatrogenic hypothyroidism, as a major clinical problem especially in people, cats, and other animal species which are treated with methimazole or other antithyroid drugs, influences numerous functions (3, 4, 10, 11, 12, 16). Naturally occurring hypothyroidism, as a systemic disease, leads to pituitary and testicular damage, especially during hypogonadotropic hypogonadism; however, other reasons for these conditions, such as testicular functional changes, have been found (7, 8, 16, 24).…”
Section: Introductionmentioning
confidence: 99%